1990
DOI: 10.1128/mcb.10.5.2104
|View full text |Cite
|
Sign up to set email alerts
|

Positive control of sporulation-specific genes by the IME1 and IME2 products in Saccharomyces cerevisiae.

Abstract: In the yeast Saccharomyces cerevisiae, meiosis and spore formation require the induction of sporulationspecific genes. Two genes are thought to activate the sporulation program: IMEI and IME2 (inducer of meiosis). Both genes are induced upon entry into meiosis, and IMEI is required for IME2 expression. We report here that IMEI is essential for expression of four sporulation-specific genes. In contrast, IME2 is not absolutely essential for expression of the sporulation-specific genes, but contributes to their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(171 citation statements)
references
References 26 publications
7
163
0
1
Order By: Relevance
“…3A); expression of HOPl preceded expression of SPSl by ~2 hr, and expres sion of DITl began 2 hr after the SPSl gene had been turned on. This sequential pattern of gene expression was consistent with previous observations (Briza et al 1990b;Mitchell et al 1990;Smith et al 1990). …”
Section: Spsl Is Expressed As Meiosis Is Nearing Completionsupporting
confidence: 81%
“…3A); expression of HOPl preceded expression of SPSl by ~2 hr, and expres sion of DITl began 2 hr after the SPSl gene had been turned on. This sequential pattern of gene expression was consistent with previous observations (Briza et al 1990b;Mitchell et al 1990;Smith et al 1990). …”
Section: Spsl Is Expressed As Meiosis Is Nearing Completionsupporting
confidence: 81%
“…They contained the complete ORFs from the G 1 cyclin gene CLN2, the B-type cyclin genes CLB1, CLB3, and CLB5, and a truncated CLB1 cDNA lacking the N-terminal 120 aa, CLB1-dN. In addition, we identified plasmids containing the entire ORF of IME2, encoding a meiosis-specific protein kinase with sequence similarities to CDKs (30,31). Immunoblotting showed that the expression of these cDNAs caused the accumulation of Clb2-lacZ protein in G 1 -arrested cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is unknown whether Ime2 also is permanently unstable during meiosis or whether it then gets periodically stabilized. Stabilization could be a mechanism to allow efficient accumulation of Ime2 in early meiosis, in addition to the transcriptional induction of the IME2 gene (31,43).…”
Section: Is Ime2 Activity Regulated By Its Stabilitymentioning
confidence: 99%
“…In the earliest stages of meiosis Ime2 positively regulates Ime1-dependent transcription of early meiosis-specific genes (14). Ime2 also appears to promote early gene transcription in an Ime1-independent fashion.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 98%